Inside view of a Huidah dwelling [electronic resource] - Deans, James, 1827-1905. ([S.l. : s.n., 1887)
Signed and dated: James Deans, Oakvale, June 10, 1884. From: The American antiquarian, v. IX no. 5, Sept. 1887. Caption title. Electronic reproduction. Mode of access: Internet. 44